THE EFFECT OF EXPERIENTIAL MARKETING ON CUSTOMER LOYALTY: THE ROLE OF CUSTOMER SATISFACTION AS A MEDIATOR - Nabila Aufa Nadya (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
This research examines experiential marketing and its effect on customer loyalty with customer satisfaction as a mediator. This research is based on two theories; expectation-confirmation theory (ECT) and satisfaction-loyalty theory. This article was made because the development of the marketing concept has grown rapidly, therefore, that it no longer focuses on its products, but focuses on its consumers, hence, that an interesting experience will provide something different for consumers to enjoy their products or services. In an effort to provide a theoretical basis for the role of customer satisfaction in mediating experiential marketing on customer loyalty, researcher propose a framework that describes consumer behavior. These are expected to have an impact on the perceived experience by customer will create satisfaction, therefore, customers become loyal. Researcher further posit that the relationships between experiential marketing and customer loyalty are indirect, but through the perceived satisfaction by customers. Finally, researcher present customer satisfaction as a mediator between experiential marketing and customer loyalty. Implications for management and future research are presented.